Temporal patterns and seasonal variation in microplastic loads in the water column and in the tissues of consumers along the southern and south-eastern coasts of South Africa - Redelinghuys, Suzanne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Plastic pollution in the marine environment has become an environmental concern and a subject of ecological research. The field of microplastic pollution in particular has expanded dramatically in the last few years. Though much data exists on the spatial variability of microplastics in the marine environment globally, little is known about temporal variability, especially on short-term time scales in the southern hemisphere. Similarly, virtually nothing is known about the temporal patterns in microplastic ingestion by marine invertebrates, despite the fact that numerous studies have demonstrated that vertebrates and invertebrates routinely ingest microplastics with varied physiological effects. This study aimed to, 1) provide base-line data for microplastic loads in the nearshore environment along the Eastern Cape Province of South Africa over four short-term time scales: daily, weekly, monthly, and yearly; and, 2) assess whether there are any seasonal patterns in microplastics ingested by selected filter-feeding consumers at two sites along the southern and south-eastern Cape coastlines of South Africa. Results for part one of this study demonstrate no temporal patterns over the different time scales considered (ANOVA, p > 0.05 in all cases). Microplastic counts ranged on average from 55 ± 289 to 930 ± 462 microplastic particles.m-3. With the exception of two instances, microfibres constituted > 50 % (range: 47 to 97 %) of the total microplastic counts. Part two of this study assessed the size range of, and seasonal and spatial patterns in ingested microplastic. No significant differences were found in the number of microplastics ingested within seasons between the mussels Perna perna (Linnaeus, 1758) and Mytilus galloprovincialis (Lamarck, 1819), and the barnacles, Octomeris angulosa (Sowerby, 1825) and Tetraclita serrata (Darwin 1954) (Student's t-test; d.f = 18; p > 0.05 in all cases), or between the two sites sampled, Kenton-on-Sea, Eastern Cape, and Wilderness, Western Cape (ANOVA; d.f. = 18; p > 0.05 in all cases). The nitric acid digestion technique was used to determine the presence of ingested microplastics. Microplastic loads ranged from 2 ± 1 to 33 ± 19 microplastics.g-1 wwt across all consumers, and the size of ingested microplastics ranged from 1 to 16 μm. Though highly variable, the absence of statistically significant differences in ingestion rates points to a ubiquity in the availability of microplastics within the water column over time and space.
Keywords: Microplastics -- South Africa -- Eastern Cape; Plastic marine debris -- South Africa -- Eastern Cape; Marine pollution -- South Africa -- Eastern Cape; Ocean circulation -- South Africa -- Eastern Cape; Marine invertebrates -- Effect of pollution on -- South Africa -- Eastern Cape; Marine animals -- Effect of pollution on -- South Africa -- Eastern Cape; Mexilhao mussel -- Effect of pollution on -- South Africa -- Eastern Cape; Mytilus galloprovincialis -- Effect of pollution on -- South Africa -- Eastern Cape; Barnacles -- Effect of pollution on -- South Africa -- Eastern Cape; Tetraclita -- Effect of pollution on -- South Africa -- Eastern Cape; Octomeris angulosa -- Effect of pollution on -- South Africa -- Eastern Cape